Soros Economic Development Fund : rethinking support for a Haiti mango processor - Rae, Douglas (London : SAGE Publications Ltd, 2017)
The Soros Economic Development Fund was used to operating in risky environments. Its mission was to make program-related equity investments in developing countries, and it had built up a sound track record in countries like Bulgaria, Liberia, and India.Haiti was another place where SEDF was investing, and since 2003 the organization had been successfully funding a microfinance institution in Port-au-Prince. SEDF had focused on financial services and logistics, but in 2009 it learned about an attractive opportunity in Haiti's agriculture sector.
Originally published: Rae, D. (2011). Soros Economic Development Fund: Rethinking support for a Haiti mango processor. 12-011. New Haven, CT: Yale School of Management, Yale University. Retrieved from: https://nexus.som.yale.edu/haiti-mangoes/.
Description based on XML content.
Keywords: elektronické knihy; electronic books; Soros Economic Development Fund; Finance -- Developing countries -- Case studies; Investments, Foreign -- Developing countries -- Case studies; Economic assistance -- Developing countries -- Case studies; Economic development projects -- Case studies